Association between lateral epicondylitis and the risk of herpes zoster development. Issue 1 (2nd January 2021) - Hsu, Chao-Yu; Ke, Der-Shin; Lin, Cheng-Li; Kao, Chia-Hung
ABSTRACT: Background: Diseases burden is associated with herpes zoster (HZ) development. However, the relationship between lateral epicondylitis (LE) and HZ remains unknown. Aim: This study investigated the association between LE and the risk of HZ development. Methods: In this study, we collected data from the National Health Insurance Research Database of Taiwan. Patients who were diagnosed as having LE for the first time between 2000 and 2012 were included in the LE cohort. Patients without LE were randomly selected from the same database for inclusion in the control cohort. The outcome of interest was the first diagnosis of HZ during the follow-up period. Results: The overall incidence rates of HZ in the LE and control cohort were 8.95 and 7.14 per 1, 000 person-years, respectively. After adjustments were made, the LE cohort had a higher hazard ratio of HZ than the control cohort [adjusted hazard ratio (aHR) = 1.23]. The risk of HZ was significantly higher in those aged 50 to 64 years (aHR = 2.05) and in those over the age of 65 years (aHR = 2.50), compared with those aged ≤49 years. The risk of HZ was significantly higher in women (aHR = 1.17). The female patients with LE had a higher risk of HZ development than controls (aHR = 1.27). Conclusion: Women with LE had a higher risk of HZ development. HZ vaccination may be needed for the female patients with LE.